Pengenalan Energy Teaching Kits Sebagai Media Energi Terbarukan pada Guru IPAS di SDN 03 Kanigoro Madiun - Yuniahastuti, Irna Tri; Maharani, Swasti; Susanti, Vera Dewi; Atmojo, Alief Arida Dhimas (Jurnal SOLMA, 2025)
Background: This community service activity aims to introduce the Energy Teaching Kit to science teachers in schools. Through this program, teachers will be given training and assistance in using the tool so that they can integrate it into the learning process effectively. Awareness of the importance of renewable energy is increasing, especially amidst the challenges of climate change and dependence on fossil fuels. Method: The implementation methods used in community service include; initial observation and problem identification, design of learning media, review, creation of learning media and modules, socialization of learning media, practice of using learning media and assistance and evaluation. Results: The Energy Teaching Kit service was carried out at SDN 03 Kanigoro, Madiun City as a way to overcome various problems regarding renewable energy learning in accordance with the applicable Merdeka Curriculum. The energy kit is very helpful for teachers in explaining the concept of renewable energy and its application in everyday life to students. From this learning media, it can improve students' understanding and motivation, sharpen critical thinking and train them to work in a team